PSYCHONEUROIMMUNOLOGY ON HERBAL DRUGS: AN OVERVIEW ALEZA - Rizvi, Aleza; Mishra, Anuradha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Psychoneuroimmunology (PNI) is the branch of biomedical science that explores the relationships between the nervous system, emotions, and the immune system. In other words, we can say that PNI is the study of the interaction between mind and body as a result of stress exposure. Therefore it is also called as mind-body medicine. It has been stated that psychological states like chronic stress, depression, anxiety, fear, and social context produce profound effects on the body. Herbal anti-stress products have the advantage of the limited side effects. Medicinal plants have been known for millennia and are highly esteemed all over the world as a rich source of therapeutic agents for the prevention of stress-related diseases like cancers, coronary disease, and some autoimmune diseases. PNI reminds us that psychological states like chronic stress, depression, anxiety, fear, and social context produce profound effects on the body. PNI explores the influence of your mind on your body and immune system. Using a variety of techniques, you direct your energies toward healing and health. The aim of this review is to highlight the plants involved in improving health through direct effects on immune function, as well as through the mind/body connection. Keywords: Psychoneuroimmunology , Stress, Ayurveda, Mind body medicine